PERAN PROGRAM OBROLAN SRIWIJAYA DALAM MELESTARIKAN BUDAYA LOKAL: STUDI KASUS LEMBAGA PENYIARAN PUBLIK RRI PALEMBANG - Meisafatrin, Fadiah; Saputra, Sepriadi; Hati, Putri Citra (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This study aims to examine the role of public broadcasting institutions, especially Pro 4 RRI Palembang, in preserving local culture through the “Obrolan Sriwijaya” program. In the era of globalization and increasingly developing digital media, local culture faces challenges in maintaining its existence. The “Obrolan Sriwijaya” program is presented as an educational media and a representation of Palembang culture, which is broadcast periodically. The research method used is descriptive qualitative with a case study approach. Data collection techniques are carried out through in-depth interviews, participatory observation, and documentation. The study results show that this program plays an important role in shaping cultural awareness, building local community identity, and setting a cultural agenda through the media. This program also succeeded in presenting cultural speakers, using local languages, and raising themes that are relevant to Palembang traditions.